Factors associated with use of verbally coercive, incapacitated, and forcible sexual assault tactics in a longitudinal study of college men. Issue 1 (January 2015) - Zinzow, Heidi M.; Thompson, Martie
<x xml:space="preserve">Abstract</x> Although verbally coerced and incapacitated sexual assaults are common, less is known about perpetrators of these incidents in comparison to perpetrators of forcible assaults. Furthermore, few studies have investigated factors that differentiate perpetrators who employ different forms of sexual assault tactics. The current study included 526 men who completed self‐report inventories at the end of each of their four years in college. Measures assessed sexual assault tactics, demographics, incident characteristics, risky behavior, rape supportive beliefs and peer norms, antisocial traits, and childhood adversity. Perpetrators were grouped based on the most severe tactics reported over the course of 7 assessed time periods, with 13% in the verbal coercion group, 16% in the incapacitation group, and 5% in the forcible group. ANOVAs determined that the forcible group scored significantly higher than incapacitation and verbal coercion groups on risky behavior, rape supportive beliefs/norms, antisocial traits, and childhood adversity. The incapacitation group scored higher than the verbal coercion group on risky behavior. In a multinomial logistic regression analysis comparing tactic groups to non‐perpetrators, all tactic groups scored significantly higher on risky behavior and rape supportive beliefs/norms, and the forcible group scored higher on antisocial traits and childhood adversity. Perpetrators in the forcible group had engaged in more repeat offenses, and perpetrators of both the incapacitated and forcible assaults were more likely to use alcohol before the incident. Findings highlight the need for interventions that are tailored to offense trajectories, alter rape supportive attitudes and peer norms, and decrease campus substance use. Aggr. Behav. 41:34–43 2015. © 2014 Wiley Periodicals, Inc.